The fundamental association between mental health and life satisfaction: results from successive waves of a Canadian national survey - Patrick Lombardo; Wayne Jones; Liangliang Wang; Xin Shen; Elliot M. Goldner (BMC, 2018)
Abstract Background A self-reported life satisfaction question is routinely used as an indicator of societal well-being. Several studies support that mental illness is an important determinant for life satisfaction and improvement of mental healthcare access therefore could have beneficial effects on a population's life satisfaction. However, only a few studies report the relationship between subjective mental health and life satisfaction. Subjective mental health is a broader concept than the presence or absence of psychopathology. In this study, we examine the strength of the association between a self-reported mental health question and self-reported life satisfaction, taking into account other relevant factors. Methods We conducted this analysis using successive waves of the Canadian Community Health Survey (CCHS) collected between 2003 and 2012. Respondents included more than 400,000 participants aged 12 and over. We extracted information on self-reported mental health, socio-demographic and other factors and examined correlation with self-reported life satisfaction using a proportional ordered logistic regression. Results Life satisfaction was strongly associated with self-reported mental health, even after simultaneously considering factors such as income, general health, and gender. The poor-self-reported mental health group had a particularly low life satisfaction. In the fair-self-reported mental health category, the odds of having a higher life satisfaction were 2.35 (95% CI 2.21 to 2.50) times higher than the odds in the poor category. In contrast, for the "between 60,000 CAD and 79,999 CAD" household income category, the odds of having a higher life satisfaction were only 1.96 (95% CI 1.90 to 2.01) times higher than the odds in the "less than 19,999 CAD" category. Conclusions Subjective mental health contributes highly to life satisfaction, being more strongly associated than other selected previously known factors. Future studies could be useful to deepen our understanding of the interplay between subjective mental health, mental illness and life satisfaction. This may be beneficial for developing public health policies that optimize mental health promotion, illness prevention and treatment of mental disorders to enhance life satisfaction in the general population.